Product Excellence in Islamic Financing at Bank Pembiayaan ‎Rakyat Syariah (BPRS) Al-Washliyah Medan - Sarah Sabila; Rahmi Syahriza; Budi Harianto (Majapahit Journal of Islamic Finance and Management, 2025)
The growth of Islamic banking in Indonesia has encouraged the emergence of various ‎financing products with competitive advantages compared to conventional banking. ‎One such example is the Bank Pembiayaan Rakyat Syariah (BPRS) Al-Washliyah Medan, ‎which offers a wide range of products based on Islamic contractual principles (akad ‎syariah). This research stems from the need to understand the distinctive advantages of ‎Islamic financing products offered by the bank and to assess the factors influencing ‎customers’ preferences for specific products. The study employs a qualitative method ‎with a field research approach. Primary data were obtained through interviews with ‎BPRS Al-Washliyah Medan employees, while secondary data were collected from ‎supporting documents and relevant literature. The aim of this study is to analyze the ‎strengths of Islamic financing products at BPRS Al-Washliyah Medan—particularly ‎those based on contracts such as murabahah, mudharabah, musyarakah, ijarah, qardh, ‎salam, and istisna—and to explore the factors shaping customer preferences for these ‎products. The findings reveal that murabahah is the most preferred product due to its ‎installment certainty and simple procedures, while other products such as mudharabah ‎and musyarakah are perceived as more complex. Flexibility, transparency, and spiritual ‎value grounded in Islamic principles have been proven to enhance customer trust. The ‎contribution of this research lies in providing insights for Islamic banking practitioners ‎in developing product strategies and serving as an academic reference to strengthen ‎the literature on customer preferences for Islamic financing products at the local level.‎